EKSISTENSI TOKOH UTAMA DALAM NOVEL“HOME $WEET LOAN” (KAJIAN PSIKOANALISIS HUMANIS DIALEKTIK) - Emmya Pepayosa Bangun; Rosmaini (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research is a qualitative descriptive study that dissects a phenomenon with words, not numbers. The data obtained are narratives and excerpts of dialogue or monologues from the novel “Home $weet Loan” by Almira Bastari. This study analyzes how the meaning and purpose of Kaluna's life, the main character in the novel “Home $weet Loan” is based on the fulfillment of her existential needs as a human being. Through Erich Fromm's dialectical humanist psychoanalytic approach, the fulfillment of human existential needs is found, which are divided into: relatedness, rootedness, transcendency, unity, and identity. Kaluna is ultimately able to achieve freedom and autonomy, and to be active according to what she believes.